Towards improving oil palm fresh fruit bunches yield in Malaysia: a system dynamics approach. (2018) - Zabid, M. Faeid M.; Abidin, Norhaslinda Zainal; Applanaidu, Shri-Dewi
Malaysia is one of the largest producers and exporters of palm oil in the world market. However, it is difficult to retain Malaysia's status as one of the biggest palm oil producers in the world with the current stagnating fresh fruit bunch (FFB) yield. The source of this problem may have come from the accumulation of ageing oil palm plantations which can be tackled through effective replanting plans. This study thus develops a system dynamics model of the oil palm plantation sector in Malaysia to understand its behaviour towards currently implemented policies. Several simulations have been performed to test various scenarios of policy interventions with the objective to reduce the accumulation of ageing area and subsequently increasing the FFB yield. The findings suggest that apart from improving the policies like promoting replanting and expanding the implementation of good agricultural practices, the most important thing is to have high commitment from planters, especially the independent smallholders, to participating in the replanting campaign.